2003
DOI: 10.1080/15389580309885
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cervical Spine Injury Risk for the 6-Year-Old Child in Frontal Crashes

Abstract: This article presents a series of 49 km/h sled tests using the Hybrid III 6-year-old dummy in a high-back booster, a low-back booster, and a three-point belt. Although a 10-year review at a level I trauma center showed that noncontact cervical spine injuries are rare in correctly restrained booster-age children, dummy neck loads exceeded published injury thresholds in all tests. The dummy underwent extreme neck flexion during the test, causing full-face contact with the dummy's chest. These dummy kinematics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…However, a safety device must prevent injuries encountered in the real world to be effective. This extrapolation from the laboratory to the real world is not always accurate, which is nicely elucidated in a study by Sherwood et al [4]. Injury tolerance studies in the laboratory on properly restrained children showed a remarkably high number of cervical spine injuries, yet these types of injuries are rarely encountered in the clinical setting.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, a safety device must prevent injuries encountered in the real world to be effective. This extrapolation from the laboratory to the real world is not always accurate, which is nicely elucidated in a study by Sherwood et al [4]. Injury tolerance studies in the laboratory on properly restrained children showed a remarkably high number of cervical spine injuries, yet these types of injuries are rarely encountered in the clinical setting.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, a vast amount of resources has been directed toward prevention and intervention strategies. Child crash test dummies have often been used for this purpose, providing an in vitro model by which to examine crash injury characteristics [4]. However, these models are limited in their ability to account for the wide spectrum of shapes and sizes in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences were attributed to a lack of spinal flexibility in the ATD. Sherwood et al 15 used modeling to compare the kinematics of a 12YO PMHS with the Hybrid III 6YO child ATD. It was shown that spinal motion is quite different in ATD and PMHS, and increasing thoracic spine flexibility generally improves biofidelity.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of the lack of biofidelity of the spine of the Hybrid III 6YO that causes a questionable prediction of the trajectory of the pediatric head and unreliable neck loads Seacrist et al, 2010;Sherwood et al, 2003). These biofidelity issues have been attributed to the rigid thoracic spine of the ATD and it is envisioned that future models of pediatric occupants (either physical or computational) will consider some degree of deformation of the thoracic spine.…”
Section: Conclusion and Contributionsmentioning
confidence: 99%